Psychometric properties of the Feeling of Unsafety Scale—Arabic in general population adults - Obeid, Sahar; Bitar, Zeinab; Malaeb, Diana; Sakr, Fouad; Dabbous, Mariam; Hallit, Souheil; Fekih-Romdhane, Feten (Frontiers in Public Health, 2025)
BackgroundFeelings of unsafety, including fear of crime, uncertainty, or insecurity, can negatively impact individuals by reducing psychological well-being and worsening health. Validating a simple and cost-effective tool to assess the general feeling of unsafety in the Arabic-speaking population, primarily residing in the Middle-East and North-Africa (MENA) region where safety can be a major concern, would be highly beneficial. The study aimed to translate the Feeling of Unsafety Scale into Arabic (FUSA) and evaluate its psychometric properties, including internal reliability, sex invariance, composite reliability, and correlation with a measure of intolerance of uncertainty.MethodsA total of 484 Arabic-speaking adults was recruited between March and April 2024. A self-administered anonymous survey was distributed through social media using a Google Forms link. We used the FACTOR software to conduct the exploratory factor analysis (EFA) of the FUSA scale and RStudio for the confirmatory factor analysis (CFA).ResultsThe confirmatory factor analysis of the unidimensional model was poor; the EFA conducted on the first split subsample showed a two-factor solution, with the CFA conducted on the second split subsample showing good fit. The latter model fit indices improved even more after adding a correlation between items 2–5 due to high modification indices. The reliability of the scale was excellent as shown by the McDonald’s omega and Cronbach’s alpha values for the total score (ω = 0.89 and α = 0.90), Factor 1 = Feeling of outdoor unsafety (ω = 0.91 and α = 0.91) and Factor 2 = Feeling of indoor unsafety (ω = 0.83 and α = 0.83). Invariance was established between males and females. Good concurrent validity was attested by positive correlations between FUSA scores and intolerance of uncertainty dimensions.ConclusionThe FUSA was found to be reliable, valid, and cost-effective for measuring the general feeling of unsafety in the general population. To evaluate its practical effectiveness and further enhance data on its construct validity, future studies should assess the scale in diverse contexts and among specific populations.